Requirement of a land compensation model to achieve the land conservation target of ‘net zero land consumption’ - Binder, Christoph (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Land is a resource that is worth protecting due to its function as a carrier for the functions of the ecosystem, recreation, climate regulation and others. The persistently high, unsustainable use of land for settlement and transport areas should therefore be limited or halted with the help of various environmental targets, such as the 30‑X hectare target by 2030 or the net-zero land take target by 2050. These targets are analysed. It becomes clear that the targets represent a vision for the future that is not very practicable, as there is a lack of concrete accounting models for implementation to date. Finally, a land compensation model is presented that is able to operationalise the environmental targets and can contribute to a concrete and practicable strategy.
Keywords: Land consumption model; 30‑X hectare target; net-zero land consumption target; land cycle management; land use; multifunctionality